53.2k views
4 votes
11. Reflecting y = – 3 sin x across the x-axis results in a function with equation

options:

A) y = 3 sin x.

B) y = – sin x.

C) y = – 3 sin (x – π).

D) y = – 3 sin (x + π).

User JvdV
by
5.3k points

2 Answers

1 vote

A y=3sin x

x-axis results in a function with equation

User Eniko
by
6.3k points
4 votes

Answer:

A

Explanation:

Reflecting y = f(x) across the x- axis, gives

y = - f(x)

Given

y = - 3sinx , then under a reflection in the x- axis

y = - (- 3sinx) = 3sinx → A

User Chelseawillrecover
by
5.3k points